2018
DOI: 10.1038/s41467-018-06860-4
|View full text |Cite
|
Sign up to set email alerts
|

Targeting SPINK1 in the damaged tumour microenvironment alleviates therapeutic resistance

Abstract: Chemotherapy and radiation not only trigger cancer cell apoptosis but also damage stromal cells in the tumour microenvironment (TME), inducing a senescence-associated secretory phenotype (SASP) characterized by chronic secretion of diverse soluble factors. Here we report serine protease inhibitor Kazal type I (SPINK1), a SASP factor produced in human stromal cells after genotoxic treatment. DNA damage causes SPINK1 expression by engaging NF-κB and C/EBP, while paracrine SPINK1 promotes cancer cell aggressivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
89
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 66 publications
6
89
0
Order By: Relevance
“…Previous studies indicate the role of AKT signaling in advancement of PCa to poorly differentiated small cell prostate carcinoma 42 . Moreover, several studies have shown a critical role of SPINK1 in activating PI3K-AKT signaling cascade in multiple SPINK1-positive cancers 11,12,15 . In concordance to these reports, we also observed a remarkable decrease in AKT signaling in LNCaP-AI-shSPINK1 cells as compared to control cells (Fig.…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicate the role of AKT signaling in advancement of PCa to poorly differentiated small cell prostate carcinoma 42 . Moreover, several studies have shown a critical role of SPINK1 in activating PI3K-AKT signaling cascade in multiple SPINK1-positive cancers 11,12,15 . In concordance to these reports, we also observed a remarkable decrease in AKT signaling in LNCaP-AI-shSPINK1 cells as compared to control cells (Fig.…”
Section: Articlementioning
confidence: 99%
“…Under normal physiological condition, SPINK1 inhibits the premature activation of pancreatic proteases, however, multiple reports have observed elevated levels of SPINK1 in cancer tissues, and shown its role in cancer progression [11][12][13][14] . Moreover, SPINK1 acts as an autocrine/paracrine factor and imparts oncogenic traits via EGFR downstream signaling 11,15 .…”
mentioning
confidence: 99%
“…7Eand Extended DataFig. 6B).However, these changes seem to be generally limited to stromal cells, rather than their adjacent epithelial cell counterparts, which have repopulated upon development of drug resistance in the course of treatment as previously characterized31,38 . We further assessed the in situ inducibility of KDM4A/B in tumor samples, and noticed substantial expression of these factors in animals experiencing MIT-involved treatments (Extended DataFig.…”
mentioning
confidence: 86%
“…However, whether SIRT1 loss is subject to NF-κB regulation remains unknown. We used Bay 11-7082 (BAY) to treat PSC27 cells, and found that SIRT1 protein level appeared even bounced upon NF-κB suppression, in sharp contrast to many of the SASP factors such as IL8 and MMP3 whose expression was markedly diminished after BAY treatment 41 To substantiate the correlation of SIRT1 with sEV production, we used suberoylanilide hydroxamine acid (SAHA) and nicotinamide (NAM), a pan-histone deacetylase (HDAC) inhibitor and a SIRT1-specific inhibitor, respectively, to treat PSC27 cells. Immunoblots indicated that expression of SIRT1, IL8 and MMP3 remained unchanged, HSP70 decreased, while sEV markers including ALIX and CD63 increased when cells were treated by either agent even in the absence of DNA damage, suggesting that SIRT1 activity is critical for the synthesis of sEV-central molecules but not for development of the SASP (Fig.…”
Section: Sirt1 Decline Supports Deficient Lysosomal Acidification Andmentioning
confidence: 99%